Two Permian sphinctozoan sponges from the Shotori Mountains (eastern Iran) - Senowbari-Daryan, Baba; Rashidi, Koorosh; Hamedani, Ali (Geologica Carpathica, 2006)
Two sphinctozoan sponge taxa, Shotorithalamia tubulara nov. gen., nov. sp. and Amblysiphonella cf. A. vesiculosa vesiculosa (de Koninck), are described from the Permian deposits of the Jamal Formation, exposed in Bagh-e Vang Mountain, and from a locality near the town of Deh-e Mohammad, both in the Shotori Mountains, north of Tabas, eastern Iran. The new genus Shotorithalamia is characterized by having ring-chambers - like Amblysiphonella - and also by possession of multibranched tubes that extended from the imperforate exo- and endowalls into the chamber interiors. The validity of families Amphorithalamiidae Senowbari-Daryan & Rigby and Girtyocoeliidae Finks & Rigby is discussed.
UnivIS-Import:2017-11-07:Pub.2006.nat.dgeo.IGM.LP.twoper
Keywords: Bagh-e Vang; Iran; Permian; Porifera; Shotori Mountains; Sphinctozoa; Taxonomy